2022
DOI: 10.18805/ijare.a-5947
|View full text |Cite
|
Sign up to set email alerts
|

​Effect of Date of Sowing on Growth, Seed Yield and Economics of Indian Mustard (Brassica juncea) Varieties under Rainfed Conditions

Abstract: Background: Indian mustard (Brassica juncea) is an important rabi crop raised under rainfed areas of Haryana. Optimum time of sowing plays an important role in augmenting the productivity of Indian mustard. There is a need to find out the optimum time of sowing of Indian mustard to overcome the yield gap under present scenario of climatic conditions. Different cultivars may respond differently to different sowing time. The current study aimed to study the effect of date of sowing on growth, seed yield and econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 6 publications
(7 reference statements)
6
21
0
Order By: Relevance
“…Akter et al (2017) reported that the use of fertilizers and organic manures in combination improved crop growth and yield in tomato. Similar results of use of fertilizers and organic manures were reported by Sharma and Singh (2011) in Brassica juncea. Singh et al (2013) recorded the parity of yield between full recommended dose of urea and diammonium phosphate (DAP) and organic matrix entrapped urea and DAP containing ¼ th of the recommended dose.…”
Section: Effect Of Treatments Of Fertilizer-manure Block On Yield And...supporting
confidence: 85%
“…Akter et al (2017) reported that the use of fertilizers and organic manures in combination improved crop growth and yield in tomato. Similar results of use of fertilizers and organic manures were reported by Sharma and Singh (2011) in Brassica juncea. Singh et al (2013) recorded the parity of yield between full recommended dose of urea and diammonium phosphate (DAP) and organic matrix entrapped urea and DAP containing ¼ th of the recommended dose.…”
Section: Effect Of Treatments Of Fertilizer-manure Block On Yield And...supporting
confidence: 85%
“…~ [6] . This was owing to a significant increase in growth and yield attributes with increasing rate of Sulphur application (Santosh Kumar et al, 2009) [16] and Jat and Mehra (2007) [11] also reported an increase in the seed and stalk yield with increasing level of Sulphur.…”
Section: Number Of Seeds Per Headmentioning
confidence: 99%
“…The experimental materials consisted of 250 stabilized F 7:8 recombinant inbred lines (RILs) mapping population of Indian mustard developed by the crossing of two contrasting parents; CS 614-1-1-100-13, a salt-sensitive mutant line developed with λ-ray irradiation treatment and stabilized for M 6 generation and CS 56, a national released high yielding salt tolerant variety by ICAR-CSSRI, Karnal (Sharma et al, 2008). These 250 RILs along with parents grown during two consecutive Rabi seasons 2020-21 and 2021-22 under control and irrigation water salinity EC iw 12 dS m À1 in the pots with three replications at Indian Council of Agricultural Research-Central Soil Salinity Research Institute (ICAR-CSSRI), Karnal (29 43'N, 76 58 0 E; 245 m above the average sea level) (Singh et al, 2020).…”
Section: Research Materials and Experimental Sitementioning
confidence: 99%